Lung Microbiome in Cystic Fibrosis - Filippo Scialo; Felice Amato; Gustavo Cernera; Monica Gelzo; Federica Zarrilli; Marika Comegna; Lucio Pastore; Andrea Bianco; Giuseppe Castaldo (Life, 2021)
The defective mucociliary clearance due to CFTR malfunctioning causes predisposition to the colonization of pathogens responsible for the recurrent inflammation and rapid deterioration of lung function in patients with cystic fibrosis (CF). This has also a profound effect on the lung microbiome composition, causing a progressive reduction in its diversity, which has become a common characteristic of patients affected by CF. Although we know that the lung microbiome plays an essential role in maintaining lung physiology, our comprehension of how the microbial components interact with each other and the lung, as well as how these interactions change during the disease’s course, is still at an early stage. Many challenges exist and many questions still to be answered, but there is no doubt that manipulation of the lung microbiome could help to develop better therapies for people affected by CF.